THE PHILOSOPHY OF SUFISM THAT ELEVATES THE SPIRIT OF ISLAM - Sardor Quvonov (Web of Journals Publishing, 2025)
This article examines the role of Sufi teachings in the Islamic world, focusing on the spiritual and ethical aspects propagated by great scholars and saints. It discusses the influence of Sufism on human psychology, moral education, and spiritual development. Special attention is given to the contributions of Arif Deggaroniy, the spiritual mentor and companion of Bahauddin Naqshband, in establishing the foundations of the Naqshbandiyya order and its widespread dissemination.
Keywords: Islam, Sufism, spiritual and moral education, ethics, Sufi, Bahauddin Naqshband, Mavlono Arif Deggaroniy.